Penerapan Pendidikan Karakter Terhadap Perilaku Merokok di SMA N 1 Batang Onang - Elina Wasila Harahap; Nurlizawati Nurlizawati; Sri Oktika Amran (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the presence of students smoking in the school environment which is a violation of school regulations. Character education is one way to reduce students' smoking behavior at school. This study looks at how the application of character education to smoking behavior at SMA N 1 Batang Onang. This study uses a qualitative case study type. The informant selection technique was purposive sampling, which was based on the researcher's criteria. Data collection was carried out by interviewing the principal, deputy head of curriculum, deputy student affairs, counseling teacher, 5 subject teachers, 16 students, and 3 parents as well as the surrounding community at SMA N 1 Batang Onang, then observing activities at school such as classrooms, cafeteria, in the parking lot, and outside the school and the latest data is in the form of documentation in the form of photos, lesson plan documents and so on. In this study using data analysis Miles and Huberman namely data reduction, data presentation, and data verification. The theory used in research on the application of character education to smoking behavior at SMA N 1 Batang Onang is Thomas Lickona's character theory. The results of this study are character education at SMA N 1 Batang Onang, application of character education at SMA N 1 Batang Onang, smoking behavior at SMA N 1 Batang Onang.